The bacterial species’ degradation activities at maximum threshold doses of glyphosate across different pH levels and temperature glyphosate biodegradation by soil bacteria at high doses under variable pH and temperature - Doolotkeldieva, Tinatin; Bobusheva, Saykal; Konurbaeva, Mahabat (Frontiers in Microbiology, 2025)
Glyphosate (N- (phosphonomethyl) glycine) is an organophosphorus compound and one of the most widely used herbicides worldwide. However, concerns about its environmental impact have prompted researchers to investigate its degradation process. This study addresses several key questions, particularly concerning the concentrations of herbicides that can inhibit the activity and disrupt the functions of degrading bacteria. Specifically, the research aims to identify the maximum glyphosate concentrations that hinder the growth and development of degradative bacteria. Three bacterial strains were tested: Stenotrophomonas sp. Ps-B, Lysinibacillus fusiformis SA-4, and Enterobacter cloacae SB-2. Glyphosate degradation was evaluated at concentrations of 50, 100, 200, 1,000, 2,500, 5,000, and 10,000 mg/L across liquid, solid, and soil media, with different pH levels and a constant temperature of 28° C. Controlled samples—both without added bacteria and containing only glyphosate—ensured the reliability of the results. Bacterial cell density was measured after 24 and 72 h using a spectrophotometer, and microbiological culture techniques were employed to quantify colony- forming units. The minimum inhibitory dose of glyphosate affecting the viability of degrading bacteria on solid nutrient media was determined via the diffusion agar method. For each strain, a specific minimum inhibitory concentration was established: 10000 mg/L for Lysinibacillus fusiformis SA-4, 5,000 mg/L for Stenotrophomonas sp. Ps-B, and 10,000 mg/L for Enterobacter cloacae SB-2. Stenotrophomonas sp. Ps-B has shown superior activity at pH levels of 8.0, 9.0, and 10.0–an important consideration for the biodegradation of alkaline soils. Complete degradation of high herbicide doses required an additional incubation period of at least 40 days. Overall, the study demonstrates that these bacterial isolates are effective in remediating soil after glyphosate application, helping prevent herbicide accumulation. Consequently, they hold promise for bioremediation of glyphosate-contaminated soils, even at high concentrations and over extended periods.